Developing of Listening Materials at the Tenth Grade Students - Syaprizal Syaprizal; Agus Triyogo; Ratna Nirwana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to develop listening material for tenth graders. The research method used is Research and Development (R&D). The results of this study indicate that the development of listening material is valid, practical and effective in the teaching and learning process. The product developed was declared valid after being evaluated by three experts with an average score of 3.86 in the